[Acute exacerbations in Chronic Obstructive Pulmonary Disease (COPD)] - Domenico Lorenzo Urso (Clinical Management Issues, 2017)
Chronic obstructive pulmonary disease (COPD) is the third leading cause of death worldwide. Acute exacerbations of COPD (AECOPD) are important events in the natural history of this condition because they negatively impact health status, rate of hospitalization, disease progression, and mortality. Viral and/or bacterial infections are the main cause of exacerbations. The treatments include systemic corticosteroids, bronchodilators, anticholinergics and/or short- or long-acting β2-agonists, and antibiotics in case of bacterial infections. In some cases, oxygen-therapy is indicated. This article focuses on several aspects of AECOPD, including epidemiology, diagnostic approach, i.e. investigations and management of AECOPD.